Перспективні методи виготовлення та ремонту електротехнічного обладнання в умовах АПК - Іноземцев, Г. Б.; Окушко, О. В. (Energy and Automation, 2017)
UDC 631.24.243PROMISING METHODS OF MANUFACTURE AND REPAIR OF ELECTRICAL EQUIPMENT IN OF AICG. Inozemtsev, O. OkushkoThe technologies used in agriculture on the stages of production, restoration and repair of electrical equipment for agricultural purposes in most cases are obsolete, enerhoresursovytratni characterized by low productivity and significant labor costs.Today in most developed countries (Germany, USA, France, Japan and others.) Implementation of the manufacturing, recovery and repair of electrical equipment for agricultural purposes is carried out using modern electrotechnologies that demonstrate high efficiency through minimization of energy and technological losses.These technologies, first of all, should include cleaning parts and assemblies of equipment of different types of pollution particularly complex configuration, welding metal and polymer materials, heat treatment, production of insulation materials and coatings with high insulation performance, improving the "finishing" operations using methods electrodeposition, electrostatic method of applying liquid and powder materials, parts recovery gas-plasma spraying and others.The purpose of research - to develop a method acoustic insulation impregnation method of ultrasonic frequencies.Materials and methods of research. It is known that a significant place in the works of repair and renewable agricultural purpose equipment manufacturing operations take to clean up various parts and components of zamaslyuvannya, dust, mechanical impurities, abrasive particles, especially in the treatment of complex configuration objects with deep holes, cavities, output scale, soot, corrosion products in almost all stages of the work.These methods require high cost of manual labor, the use of expensive, flammable solvents. In addition, they do not always, particularly in parts and components of complex configuration, providing high quality cleaning of surfaces that adversely affects the efficiency and interaction during their operation.Results. Our experience gives every reason to offer these works use acoustic vibrations of ultrasonic range, especially for small workshops, farms and so on.The disadvantages of the existing methods are great and materialovytraty of labor, incomplete treatment facilities processing that affects the electrical, mechanical and chemical resistance, weight, etc. of the object.The accumulated experience and our research shows efficacy in these various operations electrotechnologies based on the use of acoustic vibrations, electromagnetic fields and corona discharge.Impregnating capillary-porous bodies to improve insulation properties, fire resistance and mechanical strength offer exercise using acoustic vibrations of ultrasonic frequency, which should cause a reduction in processing time 1.5 ... 12 times, uniform penetration of working solutions (insulating varnishes, electrolytes, etc.). to 98%, increase the penetration depth of 30 ... 60 mm (normal methods of depth 1 ... 5 mm), reducing energy consumption up to 50 - 60% by reducing the processing time.For example, the ultrasonic processing treatment is performed at a frequency of 18 ... 24 kHz solution temperature 19 ... 21 ° C for 8 ... 10 minutes at intensity 0.5 ... 5.0 W / cm2, the volume capacity of treatment depends on the size processing facilities and ranges from 0,5 to 1,5m3.The power of such a facility with up to 100 - 500 liters of 0.5 - 1.0 kW, and for processing of products of small size to 0.2 - 0.3 kW. The main materials treatment is thermosetting and silicone coatings, such as BT, FL, CA, which represent a solid foundation in various solvents.Treatment of wooden materials to improve mechanical and operational strength to use different electrolytes.Enough effective methods of treatment for different insulation solutions, electrolytes and especially thin sheet materials, such as glass fiber makes STЭF, caste-B, ZHSP, Varnished Marks LSHM, LPC etc. and wood origin are methods based on simultaneous use of variable and constant electromagnetic fields, where the effect of treatment is due to the action of variable pressure working on solutions.Despite the high technical and economic indicators and widespread use of electrostatic method in various fields, its implementation in terms of AIC and almost not made.A major positive electrostatic implementation of the method is that it not only reduces the loss of thick paint and varnish materials (1.5 - 1.75 times), but also improves the operational stability of the coating (1.2 - 1.5), while improving this ecological conditions. Of particular note is the use of powder materials based on polyethylene, polyurethane, thermoplastic resins that create resistant coatings on parts of agricultural machinery, which is difficult temperature and humidity and corrosive environments.ConclusionsThe proposed processes in repair shops for agricultural purposes using methods electrotechnologies (acoustic vibrations, electromagnetic fields and so on.) Can provide a reduction in energy and resursovytrat by 30 - 40 and 60% to 60% of labor input, reducing processing time depending on purpose processing in 5 ... 12 times.